Consequences of the Spanish integration in the EU on the trade of Catalonia - Jose Ramon Garcia; Andreu Sanso (European Regional Science Association (ERSA), 1998)
The aim of this paper is to analyse, according to the new trade theories, the changes in the trade of Catalonia -a Spanish region- from the trade liberalisation due to the Spanish integration in the European Community. Concretely we examine if the changes in trade are predominantly of the intra-industry type or on the contrary they are, above all, of inter-industry type. Measures of intra-industry trade (IIT), marginal intra-industry trade (MIIT) and unmatched changes in trade are examined and calculated using the SITC classification on Catalonia for the years 1985 and 1994, studying the share of these changes as well as their amount. This research allows us to determine the consequences of trade liberalisation in the sense that the change in the pattern of trade triggers off other outstanding effects, specially referred to the structural adjustment. The adjustment costs are expected to be lower if the increase of the trade is of the intra-industry type since in this case the adjustment will imply productive factors moving within the same industry. These adjustment costs are analysed relating the measures of MIIT to structural economic variables such as production. Keywords: Regional Integration, Adjustment Costs, Intra-Industry Trade.
Keywords: 330